MANAJEMEN STRATEGIS PADA USAHA FASHION DI ERA DIGITALISASI MENGGUNAKAN ANALISIS SWOT - Alfian Saputra; Tyna Yunita; Franco Nero Rupelu; Chuck Noris Rupelu (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Fashion zone management is becoming more competitive as more shops, such as noneda stores, enter the market and use social media platforms such as Instagram to drive sales. This research discusses the problem of noneda store marketing strategies and industrial growth in the digitalization era. Noneda Store uses swot analysis in its strategic management. The purpose of this study is to use a SWOT analysis to consider the strategic management of noneda stores in the digitalization era. Descriptive qualitative research is the methodology used. An example of this research is the owner and eleven employees of a noneda store on Jalan Raya Galaxy Bekasi. Shop owner noneda is used as a research illustration. Methods of collecting information using observation, interviews, and documentation, as well as taking samples with a sampling tool. One of the strategies in this research is a SWOT analysis. The findings of this study indicate that noneda stores are in a growth strategy quarter, suggesting that noneda stores will benefit greatly from executing the SO strategy. Regarding reward and mudhora in Islam, this technique has the benefit of being able to reach a larger market and increase sales, while mudhorot can lead to unhealthy competition.